2022
DOI: 10.1038/s41598-022-17539-8
|View full text |Cite
|
Sign up to set email alerts
|

Prediction of phonon-mediated superconductivity in new Ti-based M$$_2$$AX phases

Abstract: A high-throughput computational method is used to predict 39 new superconductors in the Ti-based M$$_2$$ 2 AX phases, and the best candidates are then studied in more detail using density functional theory electron–phonon coupling calculations. The detailed calculations agree with the simple predictions, and Ti$$_2$$ 2 AlX … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
5

Citation Types

7
30
0

Year Published

2023
2023
2024
2024

Publication Types

Select...
5
1

Relationship

0
6

Authors

Journals

citations
Cited by 16 publications
(37 citation statements)
references
References 50 publications
7
30
0
Order By: Relevance
“…We then used this model on the full set of 13 M elements (with both A: Ge and Sn) and found that M=Cr was predicted to have the highest T c both times. Combining the insights from our previous studies [2,3] on the effect of changing A and X for fixed M, this suggested that Cr 2 AlN should be the best combination. To be robust we used this initial screening to identify the 5 best values of M (M: Ti, Cr, Fe, Nb and Mo) for further study in case the ranking changed as we varied A and X.…”
Section: Introductionmentioning
confidence: 57%
See 4 more Smart Citations
“…We then used this model on the full set of 13 M elements (with both A: Ge and Sn) and found that M=Cr was predicted to have the highest T c both times. Combining the insights from our previous studies [2,3] on the effect of changing A and X for fixed M, this suggested that Cr 2 AlN should be the best combination. To be robust we used this initial screening to identify the 5 best values of M (M: Ti, Cr, Fe, Nb and Mo) for further study in case the ranking changed as we varied A and X.…”
Section: Introductionmentioning
confidence: 57%
“…Nb 2 GeC has the highest experimental T c =10 K of any of these compounds currently known [30]. In a recent paper on Ti-based M 2 AX phases, we predicted Ti 2 AlN would have T c =13.0 K, which was the highest superconductivity temperature of all the materials studied [3].…”
Section: Introductionmentioning
confidence: 73%
See 3 more Smart Citations